2020
DOI: 10.1002/cfp2.1095
|View full text |Cite
|
Sign up to set email alerts
|

Millennials' adoption of personal financial management (PFM) technology and financial behavior

Abstract: This paper uses the Technology Acceptance Model to analyze the factors associated with personal financial management technology (PFM) adoption among millennials and extends the analysis to understand how PFM adoption is associated with financial behavior. Data from the 2018 National Financial Capability Study was used for this analysis. Evidence suggests that millennials engaging in digital side hustles, such as Uber or Lyft, are significantly more likely to adopt PFM technology. Individuals experiencing highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…According to Yoshino et al (2020), financial behavior plays an important role in FinTech adoption. Walsh and Lim (2020) found financial behavior as one of the key factors that influence personal financial management technology adoption in their study on millennials' adoption of personal financial management technologies. With more financial know-how, and positive financial behaviors in households over the generations and FinTech in their everyday activities, strong network externalities will further increase in adoption of FinTech, and with the B40 population in Malaysia, it was further proved by Magli et al in 2021.…”
Section: Financial Behaviourmentioning
confidence: 99%
“…According to Yoshino et al (2020), financial behavior plays an important role in FinTech adoption. Walsh and Lim (2020) found financial behavior as one of the key factors that influence personal financial management technology adoption in their study on millennials' adoption of personal financial management technologies. With more financial know-how, and positive financial behaviors in households over the generations and FinTech in their everyday activities, strong network externalities will further increase in adoption of FinTech, and with the B40 population in Malaysia, it was further proved by Magli et al in 2021.…”
Section: Financial Behaviourmentioning
confidence: 99%
“…Racial/ethnic differences in financial technology adoption Previous studies have documented a difference in general use behaviors related to innovative technology by race and ethnicity. Several studies have reported that compared to Caucasian/ Whites, racial/ethnic minorities have adopted mobile banking to a greater extent (Blanco et al, 2017;Federal Deposit Insurance Corporation, 2020;Federal Reserve Board, 2016), rely on mobile investment recommendations, make investments using a mobile device (Fan, 2022) and use personal financial management (PFM) technology (Walsh and Lim, 2020). However, the percentage of online banking users was higher among Whites (26.7%) compared to Blacks (12%), Hispanics (11.1%), Asians (25.7%) and Native Americans/Alaska Natives (17%) in 2019 (Federal Deposit Insurance Corporation, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, a limitation of their study was that the variables included in the model were primarily sociodemographic variables. Given that many other innovative technology acceptance-related studies have included behavioral factors (De Luna et al, 2019;De Reuver et al, 2015;Garrett et al, 2014;Li et al, 2020;Walsh and Lim, 2020), the findings from Blanco et al (2017) provide only partial implications. In addition, the study compared only Whites, African Americans and Hispanics, but excluded Asians and other populations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations